Cancer cell transmission via the placenta. Issue 1 (14th April 2018) - Greaves, Mel; Hughes, William
Abstract: Cancer cells have a parasitic propensity in the primary host but their capacity to transit between individuals is severely restrained by two factors: a lack of a route for viable cell transfer and immune recognition in allogeneic, secondary recipients. Several examples of transmissible animal cancers are now recognised. In humans, the only natural route for transmission is via the haemochorial placenta which is permissive for cell traffic. There are three special examples of this occurring in utero : maternal to foetus, intraplacental twin to twin leukaemias and choriocarcinoma-extra-embryonic cells to mother. We discuss the rare circumstances under which such transmission occurs.